Law in its own right - Olsen, Henrik Palmer (Legal theory today., 1999)
What, precisely, is the relationship between legality and morality? Does legal validity rest upon moral validity? Are legal obligations moral obligations? For some years now schools of jurisprudential Naturalism and Positivism have become increasingly ambiguous in their responses to these questions. Olsen and Toddington argue that equivocation on the central issue here - that of obligation - has brought legal theory to the point where leading legal positivists and natural lawyers no longer retain significant differences. Instead, they allege, we are left with the remnants of what has always be.